Changes of angiogenin serum concentrations in the perinatal period - Malamitsi-Puchner, A.; Sarandakou, A.; Giannaki, G.; Rizos, D.; Phocas, I. (Pediatric Research, 1997)
The polypeptide angiogenin, a normal constituent of human plasma, might be involved in endothelium homeostasis, angiogenesis, and neovascularization accompanying various diseases. This study aimed at determining angiogenin serum concentrations in the perinatal period of healthy newborns and at forming a baseline for this protein, which in the future may serve as a diagnostic index in developmental errors of the placenta and/or newborn. One milliliter of blood was drawn on d 1 and 4 of life from 30 healthy full-term neonates, and angiogenin serum concentrations were measured by an enzyme immunoassay using a commercially available kit. In 10 cases angiogenin serum concentrations were also measured in the maternal serum before delivery and in the umbilical vein serum. Angiogenin serum concentrations (μg/L) were significantly higher in maternal serum (225.7 ± 49.6) compared with umbilical vein serum (119.0 ± 34.2) (p < 0.0002), as well as that compared with day 1 (166.4 ± 44.9) (p < 0.01) but not to d 4 neonatal serum (240.8 ± 52.6). Angiogenin serum concentrations showed a statistically significant increase from d 1 to 4 (p < 10-7), as well as from umbilical cord serum to d I neonatal serum (p < 0.0002). A statistically significant correlation existed between values in umbilical cord serum and d I neonatal serum (r = 0.84, n = 10, p < 0.002) and between those in d I and 4 neonatal serum (r = 0.37, n = 30, p < 0.04). Sex, birth weight, or mode of delivery did not influence angiogenin serum concentrations. We conclude that a rapid increase of angiogenin serum concentrations to maternal levels takes place during the first four postnatal days in healthy full-term neonates.